2018
DOI: 10.21276/ijcmr.2018.5.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Related Acute Kidney Injury; Our Experience at Tertiary Level Hospital

Abstract: Introduction: Pregnancy-related acute kidney injury (AKI) is a common occurrence and is associated with substantial maternal morbidity and mortality in developing countries. It may comprise up to 25% of the referrals to dialysis centers in developing countries. Acute kidney injury in pregnancy bears a high risk of bilateral renal cortical necrosis and consequently chronic renal failure. Study aimed to evaluate the contributing factors responsible for pregnancy-related Acute kidney injury and to assess the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…This was near the findings of (Parween et al) (80%) but was higher than the reported 61.53% cases observed by (Goplani et al), 50% as observed by (Prakash et al) and 44.4% observed by (Kute et al). [10][11][12][13] A study from South India showed that 31.8% of the patients suffering from sepsis had expired, which was higher than that observed in our study (15.9%). 14 In our study, out of the total patients who had severe anaemia, 45.4% had improved renal function, 36.3% had no recovery of renal function and 18.1% expired, whereas (Kute et al) noted that 45% recovered, 20% had no recovery of renal function and as high as 35% expired out of the total patients having severe anaemia.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This was near the findings of (Parween et al) (80%) but was higher than the reported 61.53% cases observed by (Goplani et al), 50% as observed by (Prakash et al) and 44.4% observed by (Kute et al). [10][11][12][13] A study from South India showed that 31.8% of the patients suffering from sepsis had expired, which was higher than that observed in our study (15.9%). 14 In our study, out of the total patients who had severe anaemia, 45.4% had improved renal function, 36.3% had no recovery of renal function and 18.1% expired, whereas (Kute et al) noted that 45% recovered, 20% had no recovery of renal function and as high as 35% expired out of the total patients having severe anaemia.…”
Section: Discussioncontrasting
confidence: 78%
“…12 A number of recent Indian studies showed similar results (52.6% recovery, 21% progression to CKD and 13.15% maternal mortality), 64.7% recovery. 7,13 (Kute et al) found a similar maternal outcome (52.64% recovery, 15.78% maternal mortality and 26.31% had no recovery of renal function). 11 A similar study from India showed a higher renal recovery rate (89.4%), lower maternal mortality (6.1%) and a lower progression to CKD (4.6%), whereas a study from Pakistan showed a worse outcome 34.2% recovery, 24.4% maternal mortality.…”
Section: Discussionmentioning
confidence: 87%
“…22 In this study, sepsis (46.9%) was the most common cause of obstetric AKI which is similar to Parween et al (49.9%). 23 Most common presentation of PRAKI in our study was oliguria (87.5%) and edema (84.3%). In our study mean hemoglobin level were (7.8 ± 1.7) gm/dl and creatinine level were (573 ± 407) µmol/l.…”
Section: Discussionmentioning
confidence: 52%
“…Acute kidney injury (AKI) is a serious complication in critically ill patients and is associated with long-term development of chronic kidney disease (CKD) with increased hospitalization time, morbidity and mortality [1,2]. Chronic renal disease is progressively increasing in south Asian countries and the reason for this spread is multifactorial.…”
Section: Introductionmentioning
confidence: 99%